Strategi Kepemimpinan dan Pengembangan Human Capital dalam Menghadapi Dinamika Organisasi Modern: Studi pada PT Telkom Indonesia - Al Sambak Odie Karim Amrulloh; Meisya Amanda; Raehan Putra Setiawan; Putri Wulandari; Muhamad Dimas Maulana; Rony Edward Utama (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to explore how human capital (HC) strategies and adaptive leadership styles contribute to improving organizational performance at PT Telkom Indonesia. By utilizing a qualitative approach based on literature review and secondary data, this study presents an integration between visionary leadership and strategic human resource management as key drivers of corporate success. The findings reveal that synergy between inclusive leadership, continuous employee training, and digital transformation in HRM positively impacts the company's competitiveness in the era of Industry 4.0. The study recommends sustainable HC strategies and active leadership involvement in designing progressive and human-centered organizational change.